The Olympic Experimental Gymnasium Program and its Association with the Prevalence of Cardiovascular Risk Factors in Adolescents: A Cross-Sectional Study - Scheer,Carlos (2019)
Abstract Background: Cardiovascular disease (CVD) is the leading cause of death worldwide. Physical activity (PA) and appropriate diet, if adopted in childhood and adolescence, may reduce the CVD burden in later life. The Olympic Experimental Gymnasium (OEG) project was implemented to increase the PA levels of students by means of regular physical exercise and healthy eating habits. Objectives: To estimate and compare the prevalence of CVD risk factors in OEG schools versus regular schools (RSch) and to examine associations between the school environment and CVD risk factors. Methods: In this cross-sectional study with a comparator group, adolescents aged 12-13 years attending three OEG schools (n = 719) and three RSch (n = 394) were evaluated after one year of the ongoing program to estimate the prevalence of overweight, pre-hypertension/hypertension, altered glycemia, and lipid profile. An α level of 0.05 was set for statistical analysis. Results: RSch students had higher odds to have high blood pressure (OR 1.86, 1.36-2.54) and to be overweight (OR 1.49, 1.13-1.98) than OEG students. Glucose levels were not altered in most cases regardless of school type, and no differences were found in lipid profile. In the sensitivity analysis stratified by gender, girls from RSch were more likely to have high body mass index than boys. Conclusions: Exposure of adolescents to the OEG policies was positively associated with an important reduction in CVD risk factors, including high blood pressure and overweight.